If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(2x + 4) = 6(5x + 2) Reorder the terms: 3x(4 + 2x) = 6(5x + 2) (4 * 3x + 2x * 3x) = 6(5x + 2) (12x + 6x2) = 6(5x + 2) Reorder the terms: 12x + 6x2 = 6(2 + 5x) 12x + 6x2 = (2 * 6 + 5x * 6) 12x + 6x2 = (12 + 30x) Solving 12x + 6x2 = 12 + 30x Solving for variable 'x'. Reorder the terms: -12 + 12x + -30x + 6x2 = 12 + 30x + -12 + -30x Combine like terms: 12x + -30x = -18x -12 + -18x + 6x2 = 12 + 30x + -12 + -30x Reorder the terms: -12 + -18x + 6x2 = 12 + -12 + 30x + -30x Combine like terms: 12 + -12 = 0 -12 + -18x + 6x2 = 0 + 30x + -30x -12 + -18x + 6x2 = 30x + -30x Combine like terms: 30x + -30x = 0 -12 + -18x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(-2 + -3x + x2) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-2 + -3x + x2)' equal to zero and attempt to solve: Simplifying -2 + -3x + x2 = 0 Solving -2 + -3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '2' to each side of the equation. -2 + -3x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + -3x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x + x2 = 0 + 2 -3x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 -3x + x2 = 2 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x2 = 2 + 2.25 Reorder the terms: 2.25 + -3x + x2 = 2 + 2.25 Combine like terms: 2 + 2.25 = 4.25 2.25 + -3x + x2 = 4.25 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = 4.25 Calculate the square root of the right side: 2.061552813 Break this problem into two subproblems by setting (x + -1.5) equal to 2.061552813 and -2.061552813.Subproblem 1
x + -1.5 = 2.061552813 Simplifying x + -1.5 = 2.061552813 Reorder the terms: -1.5 + x = 2.061552813 Solving -1.5 + x = 2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 2.061552813 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 2.061552813 + 1.5 x = 2.061552813 + 1.5 Combine like terms: 2.061552813 + 1.5 = 3.561552813 x = 3.561552813 Simplifying x = 3.561552813Subproblem 2
x + -1.5 = -2.061552813 Simplifying x + -1.5 = -2.061552813 Reorder the terms: -1.5 + x = -2.061552813 Solving -1.5 + x = -2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -2.061552813 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -2.061552813 + 1.5 x = -2.061552813 + 1.5 Combine like terms: -2.061552813 + 1.5 = -0.561552813 x = -0.561552813 Simplifying x = -0.561552813Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.561552813, -0.561552813}Solution
x = {3.561552813, -0.561552813}
| 8w+3-10w= | | 2w-11w=-12 | | 7.9=2n-5 | | y+y+x+39=180 | | X+X+10=56 | | 25a^3+20a^2+3a= | | 7x-12=4x-9 | | 131/3x2/3 | | x-5/4-x-4/5=1/2-x/10 | | 4.8=2.1-0.5y | | 1/4×20 | | 4.7=2.4-0.7y | | N-3=15/5 | | 4(5x+2)=100+8 | | f(x)=3x-1/2x^2 | | f(x)=3x-1/x^2 | | f(x)=-8ex+7x-4 | | 110a+30=90-10a | | (6+2x)(11+2x)=94 | | 3q+2q+q-6q+2q=18 | | 9a-15=39 | | 5/2/50=x/80 | | 3x-4=0.5x+7 | | f(x)=3x*ln(3x) | | 9x-136+6x-76=180 | | 12k-10k+4K+4K=20 | | 15=3/8w | | (5*x)/10=-7/(3*x) | | 2n^2+4n+6=4 | | 1/3÷5/6 | | m-6m+3m-5= | | 16x+260y=4 |